2021
DOI: 10.4236/ojmm.2021.112009
|View full text |Cite
|
Sign up to set email alerts
|

Phenotipic Prevalence of Antibiotic Resistance in Gabon

Abstract: Background: The increasing phenomenon of bacterial resistance to antibiotics is a real public health problem. The main causes are poor management of hygiene and water quality, but also the use of antibiotics without precaution. The objective of this study was to isolate and determine the antibiotic resistance profile of the different bacteria found in the main hospitals and bacteriology laboratories in Gabon. Methods: 6034 samples were taken from hospitals in seven main cities of Gabon, and analyzed according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Similar rates of MDR uropathogenic strains have been previously described in Gabon [15]. However, a lower rate of MDR isolates was reported by Dikoumba et al [29]. The differences observed could be explained by the origin of the samples used in each study.…”
Section: Discussionsupporting
confidence: 75%
“…Similar rates of MDR uropathogenic strains have been previously described in Gabon [15]. However, a lower rate of MDR isolates was reported by Dikoumba et al [29]. The differences observed could be explained by the origin of the samples used in each study.…”
Section: Discussionsupporting
confidence: 75%
“…In line with this, previous studies conducted between 2008 and 2012 in Lambaréné observed MRSA rates of 6–11% [ 14 , 20 ]. Similarly, a prospective multi-center study conducted between 2016 and 2018 in Gabon found a rate of 16% MRSA among all S. aureus isolates [ 15 ]. While the above studies included isolates from all types of infections, a study conducted in several Sub-Saharan African countries, including Gabon, on the management of S. aureus SSTI detected 6.5% MRSA [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that the prevalence of MRSA-associated SSTI in Africa may exceed 50% [11][12][13]. In developing countries, such as Gabon, antibiotic resistance poses a major public health threat, but studies investigating the prevalence of antimicrobial resistance are limited [14,15]. Data on temporal changes in the proportion of MRSA (among all S. aureus) causing SSTI in Gabon are currently not available.…”
Section: Introductionmentioning
confidence: 99%
“…Weak resistance of S. aureus strains has been recorded with ciprofloxacin, amikacin, and gentamicin. The Gabon study on urine samples showed low resistance rates of S. aureus isolates to amikacin and gentamicin [ 45 ]. A low resistance rate to ciprofloxacin, amikacin, and vancomycin was recorded in the CNS.…”
Section: Discussionmentioning
confidence: 99%